Psoriasis and periodontitis: Exploring an association or lack thereof - Shipra Gupta; Sunil Dogra; Gurparkash Singh Chahal; Savita Prashar; Angadveer Pal Singh; Mili Gupta (Wolters Kluwer Medknow Publications, 2021)
Objectives: Psoriasis is a common, chronic, non-communicable skin disease with no clear etiology or cure. Periodontitis is a chronic inflammatory condition which is now known to significantly influence various systemic diseases as an established risk factor. This study aimed at comparatively evaluating the periodontal status of Psoriatic patients vis. a vis. that of age and gender matched systemically healthy volunteers. An attempt was also made to explore a possible association, if any, amongst the two diseases. Materials and Methods: Forty two residents of Chandigarh, suffering from Psoriasis and attending the Psoriasis Clinic of Department of Dermatology & Venereology, Post Graduate Institute of Medical Education & Research, Chandigarh were recruited over a period of 10 months (Case group) and their periodontal status was compared with forty two age and gender matched systemically healthy volunteers (Control group) randomly selected from the Out Patient Department of Periodontics, Dr. Harvansh Singh Judge Institute of Dental Sciences & Hospital, Panjab University, India. Their serum IL-33 levels were evaluated and compared in an attempt to identify an underlying common pathological pathway. Results: The periodontal status was comparable in the two groups in terms of the debris index (p = 0.932), calculus index (p = 0.088), plaque index (p = 0.097), and mean clinical attachment loss (p = 0.401). A higher bleeding points index was recorded amongst healthy individuals as compared to the Psoriasis group, the difference being statistically significant (p = 0.001). The mean number of teeth were more in the Psoriasis group as compared to the healthy group (p=0.034). IL 33 levels were also not significantly different (p = 0.491). Conclusion: Contrary to currently available evidence in literature, the study did not find a statistically significant association between Psoriasis and Inflammatory Periodontal Disease.